APLIKASI EDIBLE FILM DARI PATI UBI JALAR KUNING YANG MENGANDUNG EKSTRAK LENGKUAS MERAH PADA DODOL UNTUK MEMPERPANJANG UMUR SIMPAN - , ATTRIKA WINDARESTI CAHYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Packaging is one of the factors affecting the quality and shelf life of the product, especially in food products. One of packaging that can be eaten along with the packaged product is called edible film. Edible film can be made from yellow sweet potato starch and red galangal extract can be added to extend the shelf life of the product, especially in the traditional food such as dodol. Edible film based from starch variation 2 % (w/v) and 3% (w/v) and sorbitol variation 30 % (w/w) and 40 % (w/w), which is seen by the tensile strength test and water vapor permeability of edible film. Then the edible film will be added with red galangal extract at concentration 0 ppm, 1000 ppm, and 10000 ppm. Edible film with the addition of red galangal extract will be applied to the packaging of Dodol. Dodol will be tested during 15 days with the observation of mold, TPC test, water content test, and peroxide value. The results showed that tensile strength of starch variation 3% (w/v) and the variation of sorbitol 30% (w/w) is 8.09 MPa, with water vapor permeability value 6.51 g.mm/m2.hari.kPa. Dodol wrapped using edible film with the addition of 10000 ppm red galangal extract can inhibit the growth of mold until 8-9 days, the test results showed that during 15 days of dodol storage the value of TPC was 3,9 x 106 CFU/gram, the water content was 24,63% and peroxide value was 2.2317 meq/kg sample.